The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1309/qhca-8594-ta7p-0dvq
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Battery of Eight Antibodies That Can Distinguish Most Cases of Epithelial Mesothelioma From Adenocarcinoma

Abstract: An immunocytochemical battery comprising 9 antibodies specifically distinguishes 80% of the epithelial malignant mesotheliomas from adenocarcinomas. The discriminatory power of antibodies to calretinin was tested together with this battery to determine whether the performance thereby could be improved. The study comprises 119 mesotheliomas of epithelial or mixed phenotype and 57 adenocarcinoma metastases in the pleural cavity. The differences between the 2 groups were highly significant for all recorded parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
9

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 16 publications
3
56
0
9
Order By: Relevance
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] The 'true' diagnoses were based on all available information in every single case; cytological, histological and autopsy diagnoses, clinical information, including the results of imaging techniques and clinical follow-up. Cases without a final diagnosis were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%